Psychological premises for research training of undergraduate students - Ordoñez, Rosa (2014)
The formative research is an integral process, sequenced, reflexive, systematic, controlled, and critical. Allowing it to discover new knowledge in any field of human development, which requires much intellectual effort to create ideas and reasoning that enable to transform the reality. The presentation of this topic has aims to propose pedagogical alternatives on the basis of their livelihood psychological, in order to improve the research skills of professor and students. It is important first to know the current reality of the formative research process to implement strategies of teaching technical skills to conduct investigations during undergraduate studies, establishing suitable terms to investigate which implies a mastery of techniques to analyze, understand, and apply scientific information directed to the solutions of problems of the world. Scientific research demands the development of skills and modes of action, aimed to interact positively and creatively with nature and society, in a responsible manner. The psychological premises of the formative research focused on the role that correspond to the investigative skills and their development based on the criteria of frequency, periodicity, flexibility, and complexity only attainable in a relationship of theory and practice.